A 2-D DCT Hardware Codec based on Loeffler Algorithm - Martisius, I.; Birvinskas, D.; Jusas, V.; Tamosevicius, Z. (Elektronika ir Elektrotechnika, 2011)
In this paper, we report a hardware implementation scheme and results of a Loeffler algorithm based 2-D discrete cosine transformcodec. This codec performs a full 2-D DCT encoding and 2-D IDCT decoding. It is fully functional, capable of being used in anyhardware coding algorithm. The Loeffler algorithm is one of the newest and most effective fast DCT algorithms for hardwareimplementation. 2-D DCT/IDCT was computed by applying 1-D operations on matrix using a row/column approach. For a hardwareimplementation, additional data buffers and control logic is used to perform 2-D transforms. Since hardware implementation is lessaccurate than mathematical modelling, more errors occur in the computational results. However, differences are small and cannot bedirectly observed. Ill. 6, bibl. 10, tabl. 3 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.611